2020
DOI: 10.3389/fcimb.2020.573735
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial Colonization From the Fetus to Early Childhood—A Comprehensive Review

Abstract: The development of the neonatal gastrointestinal tract microbiota remains a poorly understood process. The interplay between neonatal (gestational age, genetic background), maternal (mode of delivery, nutritional status) and environmental factors (antibiotic exposure, available nutrition) are thought to influence microbial colonization, however, the exact mechanisms are unclear. Derangements in this process likely contribute to various gastrointestinal diseases including necrotizing enterocolitis and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 203 publications
(246 reference statements)
1
41
0
4
Order By: Relevance
“…Although some studies have defined the microbial composition of the fetal meconium has been defined in several studies ( Moles et al, 2013 ; Stinson et al, 2019 ), others have linked premature birth with the decreased microbial diversity within the meconium microbiome ( Ardissone et al, 2014 ). Interestingly some recent studies suggest a similarity within the microbial profile in between placenta, fetal meconium, and amniotic fluid ( He et al, 2020 ; Senn et al, 2020 ). Younge et al have confirmed maternal-fetalin utero-translocation of the gut microbiota using a mouse model ( Younge et al, 2019 ).…”
Section: Development Of Gut Microbiotamentioning
confidence: 99%
“…Although some studies have defined the microbial composition of the fetal meconium has been defined in several studies ( Moles et al, 2013 ; Stinson et al, 2019 ), others have linked premature birth with the decreased microbial diversity within the meconium microbiome ( Ardissone et al, 2014 ). Interestingly some recent studies suggest a similarity within the microbial profile in between placenta, fetal meconium, and amniotic fluid ( He et al, 2020 ; Senn et al, 2020 ). Younge et al have confirmed maternal-fetalin utero-translocation of the gut microbiota using a mouse model ( Younge et al, 2019 ).…”
Section: Development Of Gut Microbiotamentioning
confidence: 99%
“…Several studies have recently detected microbe traces in human placenta and fetal samples (Aagaard et al, 2014;Al Alam et al, 2020;Ardissone et al, 2014;Biasucci et al, 2008;Cao et al, 2014;Collado et al, 2016;Funkhouser and Bordenstein, 2013;de Goffau et al, 2019;Diaz Heijtz, 2016;Jimé nez et al, 2005;Kundu et al, 2017;Parnell et al, 2017;Perez-Muñ oz et al, 2017;Romano-Keeler and Weitkamp, 2015;Seferovic et al, 2019;Stout et al, 2013;Willyard, 2018;Younge et al, 2019). However, active microbial presence in utero is still a topic of constant debate, and novel sensitive approaches are required to understand the complexities of human gestation (Collado et al, 2016;Fricke and Ravel, 2021;Perez-Muñ oz et al, 2017;Robertson et al, 2019;Senn et al, 2020;Silverstein and Mysorekar, 2021;Stinson et al, 2019). Thus, we explored the presence of microbes in fetal tissues and their potential role in priming and activation of memory T cells during fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…First successful experiments with apical-out organoids and microorganisms have already been performed by Co et al (2019) , Li et al (2020) , Nash et al (2021) , but so far solely adult stem cell-derived organoids could be used for this. In case of PSC-derived organoids, microbial colonization and pathogen infections can be studied at different stages of development, which is particularly important since the early stages of gut microbiota development remains poorly understood ( Senn et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%